Comparative Palynological, Physicochemical, Antioxidant and Antibacterial Properties of Romanian Honey Varieties for Biomedical Applications. Issue 8 (4th July 2022) - Iosageanu, Andreea; Mihai, Elena; Prelipcean, Ana‐Maria; Anton, Ruxandra Elena; Utoiu, Elena; Oancea, Anca; Craciunescu, Oana; Cimpean, Anisoara
Abstract: The aim of this study was to investigate the melissopalynology, physicochemical characteristics, antioxidant and antibacterial activity of seven honey samples harvested from different geographical regions and climates of Romania. The melissopalynological analysis revealed that monofloral and multifloral samples contained a wide diversity of minor pollen types from Romanian flora. The moisture, pH and free acidity values were within international limit. HPLC analysis indicated high content of fructose and glucose and low content of sucrose. Bioactive compounds including proteins, phenolics, flavonoids and ascorbic acid were present in variable quantities, according to the botanical origin and geographical area. The highest phenolics and ascorbic acid content was in multifloral honeys from Crisana mountain and meadow and the extrafloral honeydew honey. The same honey samples have exerted free radical scavenging and antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa . The free radical scavenging activity was strongly correlated to phenolics and ascorbic acid content, while the antimicrobial activity was medium correlated only to phenolics content. In conclusion, the selected Romanian honey samples with best antioxidant and antimicrobial activity could be further tested for the development of novel biomedical products. Abstract :